2013
DOI: 10.1155/2013/546709
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Thrombi in the Suprahepatic Inferior Vena Cava: The Cardiothoracic Surgeons’ View

Abstract: Background. Retroperitoneal tumours propagate intrathoracic caval tumour thrombi (ICTT) of which we consider two subgroups: ICTT-III (extracardiac) and ICTT-IV (intracardiac). Methods. Case series review. Results. 29 series with 784 patients, 453 with extracardiac and 331 with intracardiac ICTT. Average age was 59 years. 98% of the tumours were RCC, 1% adrenal and Wilms' tumours, and 1% transitional cell carcinomas. The prevalent incision was rooftop with or without sternotomy. Mortality was 10% (5% for ICTT-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
(74 reference statements)
0
6
0
3
Order By: Relevance
“…To the presented case a Chevron/Kocher incision was performed first to allow mobilization of the liver and the right kidney and exposure of the IVC, followed by a separate median sternotomy. CPB with or without DHCA is the traditional approach to obtain a bloodless field for thrombectomy in patients with atrial involvement [ 2 , 5 ]. DHCA was questioned due to longer operative times, higher postoperative coagulopathy, renal failure and retroperitoneal hemorrhage but a recent review of the literature demonstrated no significant difference to the outcome with or without hypothermia [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the presented case a Chevron/Kocher incision was performed first to allow mobilization of the liver and the right kidney and exposure of the IVC, followed by a separate median sternotomy. CPB with or without DHCA is the traditional approach to obtain a bloodless field for thrombectomy in patients with atrial involvement [ 2 , 5 ]. DHCA was questioned due to longer operative times, higher postoperative coagulopathy, renal failure and retroperitoneal hemorrhage but a recent review of the literature demonstrated no significant difference to the outcome with or without hypothermia [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Renal cell carcinoma (RCC) is characterized by its high metastatic index and its propensity to invade intravascular and generate tumor thrombi. Approximately 15% of all RCCs will invade the inferior vena cava (IVC) but only 1% of them will extend supradiaphragmatic into the right atrium, classified as a Level IV tumor thrombus according to the Neves and Zincke system [ 1 , 2 ]. Total surgical resection is the gold standard of therapy in these patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ñåðéîçíèì òåõí³÷íèì çàâäàííÿì º êîíòðîëü âåðõ³âêè ïóõëèííîãî òðîìáó ïðè éîãî íàää³àôðà´ìàëü-í³é ëîêàë³çàö³¿. Òðàäèö³éíî ó äàíî¿ êàòå´î𳿠õâîðèõ âèêîðèñòîâóþòü òåõíîëî´³¿ øòó÷íîãî êðîâîîá³ãó [2,5,6,7]. Çà îñòàíí³ ðîêè âñå ÷àñ-ò³øå ïîâ³äîìëÿþòü ïðî àëüòåðíàòèâí³ õ³ðóð-³÷í³ ï³äõîäè äî ñóïðàä³àôðà´ìàëüíîãî â³ää³ëó ÍÏ âèêëþ÷íî ç áîêó ÷åðåâíî¿ ïîðîaeíèíè [2,4,7].…”
Section: ðåçóëüòàòè é îáãîâîðåííÿunclassified
“…²íòðàîïåðàö³éíà àâòîãåìîòðàíñôóç³ÿ ³ç çàñòîñóâàííÿì àïàðàòó "Ñell-Saver" (Íaemonetics) äîçâîëèëà ñóòòºâî çìåíøèòè îá'ºì êðîâîâòðàòè òà ïîòðåáó â äîíîðñüê³é êðîâ³, ³ ÿê íàñë³äîê öüîãî -çíèçèòè ðèçèê ³íôåêö³éíèõ óñêëàäíåíü, êîàãóëîïàò³é òà ³ìóíîñóïðåñ³é [1,6,8].…”
Section: ðåçóëüòàòè é îáãîâîðåííÿunclassified
“…Îïåðàö³éíà òàêòèêà ë³êóâàííÿ õâîðèõ íà ÍÊÐ ç âåíîçíèì òðîìáîçîì IV ð³âíÿ ïîòðåáóº ³íäèâ³äóàëüíîãî ï³äõîäó òà ïîâèííà âêëþ÷àòè îö³íêó îáñÿãó óðàaeåííÿ ÍÏ ïóõëèíîþ. Íàää³àôðàãìàëüíèé òà âíóòð³øíüîïåðåäñåðäíèé ð³âí³ ïóõëèííîãî òðîìáîçó âè-êëþ÷àþòü çàñòîñóâàííÿ êàâà-ô³ëüòðà òà âèìàãàþòü ïðîâåäåííÿ òîðàêî-àáî ñòåðíîëàïà-ðîòî쳿 ç âèêîðèñòàííÿì åêñòðàêîðïîðàëüíîãî êðîâîîá³ãó, îñîáëèâî ïðè ù³ëüíèõ ô³êñîâàíèõ, ôëîòóþ÷èõ âíóòð³øíüîïåðåäñåðäíèõ àáî ïðîëàáóþ÷èõ ó ïðàâèé øëóíî÷îê âåðõ³âêàõ òðîìá³â [2,3,9,11,17,18,20]. Âèêîðèñòàííÿ ãëèáîêî¿ ã³ïîòåð쳿 òà çóïèíêè êðîâî-îá³ãó äîçâîëÿº ïåâíîþ ì³ðîþ óíèêíóòè äî-…”
unclassified